Multi-scale analysis of social network based on diffusion wavelets - Guo-wei SHEN; Wu YANG; Wen-ting HUANG; Wei WANG; Li DING; Miao YU (Tongxin xuebao)
A new multi-scale framework based on diffusion wavelets was proposed to analyze the homogeneous relationships,which can be used to conduct multi-scale analysis on structures,contents and user behaviors.The diffusion operator of diffusion wavelet only considers the local similarity in this framework.The experiments on both synthetic and real-world networks show that the proposed algorithm outperforms the typical algorithms in multi-scale analysis without parameters.